2002
DOI: 10.1007/s00464-001-8321-5
|View full text |Cite
|
Sign up to set email alerts
|

Hand-assisted laparoscopic gastric bypass does not improve outcome and increases costs when compared to open gastric bypass for the surgical treatment of obesity

Abstract: The Hand-Lap GB yielded good weight reduction in a population of morbidly obese patients, but at a higher cost for hospital care than Open GB. There was no decrease in the incidence of incisional hernias with the Hand-Lap GB procedure. Although Hand-Lap GB appears to be safe and effective, its failure to provide a decrease in hospital stay or risk of incisional hernia requiring subsequent surgical repair is significant. The primary role for the Hand-Lap GB procedure should therefore be to aid surgeons in devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 7 publications
1
11
1
Order By: Relevance
“…Weight loss was similar in both groups, as were postoperative complications. DeMaria et al confirmed these results in a nonrandomised study (EL 2b [74]). …”
Section: Surgical Access: Open Vs Laparoscopicsupporting
confidence: 76%
“…Weight loss was similar in both groups, as were postoperative complications. DeMaria et al confirmed these results in a nonrandomised study (EL 2b [74]). …”
Section: Surgical Access: Open Vs Laparoscopicsupporting
confidence: 76%
“…Marginal ulceration is a well-known complication of Rouxen-Y gastric bypass occurring in 1% to 16% of patients [14][15][16]. In our series, the incidence of stomal ulceration is 10.7%.…”
Section: Discussionmentioning
confidence: 59%
“…Paradoxically, Angus et al 10 demonstrated that the hospital costs of bariatric surgery were higher (US$ 11,773.00) in the public health system (Medicare and Medicaid) compared to private care (US$ 4,435.00). Several other authors have reported widely varying costs ranging from US$ 7,800.00 to US$20,500.00 4,[11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%